2018
DOI: 10.1093/dote/doy089.fa06.05
|View full text |Cite
|
Sign up to set email alerts
|

FA06.05: Detecting Residual Esophageal Cancer After Neoadjuvant Chemoradiation by Endoscopic Biopsies, Eus and FDG-Pet: A Systematic Review and Meta-Analysis

Abstract: Background After curatively intended neoadjuvant chemoradiotherapy (nCRT) according to CROSS plus surgery for esophageal cancer, 29% of patients have a pathologic complete response. Active surveillance after nCRT, in which patients undergo frequent clinical examinations and where esophagectomy is only offered to those with a locoregional regrowth without distant metastases, has been proposed as novel treatment option. This study provides a systematic review and meta-analysis of the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Many clinical trials have been conducted to identify the value of PET parameters to predict pathological response. Several meta-analyses have indicated that 18 F-FDG PET/CT images were unable to accurately detect pathological response, the sensitivities and specificities were 60%-70% [20][21][22]. Most of these studies used SUVmax or percentage reduction of SUVmax as criterion.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical trials have been conducted to identify the value of PET parameters to predict pathological response. Several meta-analyses have indicated that 18 F-FDG PET/CT images were unable to accurately detect pathological response, the sensitivities and specificities were 60%-70% [20][21][22]. Most of these studies used SUVmax or percentage reduction of SUVmax as criterion.…”
Section: Discussionmentioning
confidence: 99%
“…Das „Re-Staging“ nach erfolgter neo-adjuvanter Therapie von Ösophaguskarzinomen und AEG-Tumoren ist in der klinischen Praxis erheblich limitiert, da die Tumoren häufig post-therapeutisch starke Regressions-Veränderungen (Nekrosen, Narben) aufweisen und entzündliche lokale Faktoren zu falsch positiven Ergebnissen bei allen bildgebenden Modalitäten führen können. Dies zeigen neue Meta-Analysen 109 110 111 deutlich, indem die gepoolte Sensitivität für CT, PET-CT, EUS und MRT zur Erfassung einer „Vollremission“ nach neo-adjuvanter Therapie zur Aufdeckung einer ypT0 – Response nur 35 % (CT), 62 % (PET-CT), < 10 % (EUS) und 80 % für das MRT betrugen. Die korrespondierende Spezifität lag dabei zwischen 73 % und 99 % (de Gouw et al).…”
Section: Primärdiagnostik Und Staging Inklusive Pathologieunclassified
“…Das „Re-Staging“ nach erfolgter neo-adjuvanter Therapie von Ösophaguskarzinomen und AEG-Tumoren ist in der klinischen Praxis erheblich limitiert, da die Tumoren häufig post-therapeutisch starke Regressions-Veränderungen (Nekrosen, Narben) aufweisen und entzündliche lokale Faktoren zu falsch positiven Ergebnissen bei allen bildgebenden Modalitäten führen können. Dies zeigen neue Meta-Analysen 100 101 102 deutlich, indem die gepoolte Sensitivität für CT, PET-CT, EUS und MRT zur Erfassung einer „Vollremission“ nach neo-adjuvanter Therapie zur Aufdeckung einer ypT0 – Response nur 35 % (CT), 62 % (PET-CT), < 10 % (EUS) und 80 % für das MRT betrugen. Die korrespondierende Spezifität lag dabei zwischen 73 % und 99 % (de Gouw et al).…”
Section: Primärdiagnostik Und Staging Inklusive Pathologieunclassified